Development and Performance Evaluation of Lime Harvesting Device - Vagadia, V. R.; Mashru, H. H.; Rank, H. D.; Prajapati, G. V.; Satasiya, R. M.; Subbaiah, R. (International Journal of Economic Plants, 2020)
Efforts were made to develop a hand tool for harvesting of lime fruits. Initially, survey was done to collect the data regarding traditional kagzilime fruit harvesting device adopted by the farmers. The problems faced with the traditional tool for lime fruit harvesting are alleviated in the JAU–Lime harvester by providing catching unit, fruit collecting mouth and conveyance pipe which reduces losses in terms of immature lime fall out and spoilage. It was compared with the traditional one in terms of number of fruits harvested per unit time, spoilage and immature fruit losses during harvesting. The average fruit harvesting capacity was recorded as 6.85 kg hr-1 and 7.83 kg hr-1 for JAU–Lime harvester and traditional harvester, respectively. The collected fruits were kept in same environment for 11 days to find the number of fruits spoiled. It was observed that up to 8th day after harvesting, no spoilage was recorded in the lime harvested by JAU-Lime harvester. It was also recorded that after 11 days nearly 36.67% of limes were spoiled from the lots which were harvested by the traditional harvester. Average fruit spoilage was observed to be 15.45 and 2.12% in traditional harvester and JAU–Lime harvester, respectively. It was also observed that due to pulling effect, an average 3.84% immature fruits fall on the ground surface, while harvesting by traditional harvester compared to 1.37% in case of JAU–Lime harvester.